2014
DOI: 10.1002/cncr.29058
|View full text |Cite
|
Sign up to set email alerts
|

Significant clinical impact of recurrent BRCA1 and BRCA2 mutations in Mexico

Abstract: Background Frequent recurrent BRCA1 and BRCA2 gene (BRCA) mutations among Hispanics, including a large rearrangement Mexican founder mutation (BRCA1 ex9-12del), suggest that an ancestry-informed BRCA-testing strategy could reduce disparities and promote cancer prevention by enabling economical screening for hereditary breast and ovarian cancer in Mexico. Methods In a multistage approach, 188 cancer cases unselected for family cancer history (92 ovarian cancer and 96 breast cancer) were screened for BRCA muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 39 publications
7
116
0
8
Order By: Relevance
“…Genomic DNA was obtained by standard methods from peripheral blood., All patients were screened for 114 BRCA mutations at a cost of <$20 USD, with a panel estimated to account for up to 75-80% of all Hispanic BRCA mutations (HISPANEL) [20]. Multiplex PCR fragments were genotyped on a Sequenom MassARRAY platform using MALDI-TOF (matrix-assisted laser desorption/ ionization -time-of-flight) mass spectrometry as previously described [11,20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was obtained by standard methods from peripheral blood., All patients were screened for 114 BRCA mutations at a cost of <$20 USD, with a panel estimated to account for up to 75-80% of all Hispanic BRCA mutations (HISPANEL) [20]. Multiplex PCR fragments were genotyped on a Sequenom MassARRAY platform using MALDI-TOF (matrix-assisted laser desorption/ ionization -time-of-flight) mass spectrometry as previously described [11,20].…”
Section: Methodsmentioning
confidence: 99%
“…Multiplex PCR fragments were genotyped on a Sequenom MassARRAY platform using MALDI-TOF (matrix-assisted laser desorption/ ionization -time-of-flight) mass spectrometry as previously described [11,20].…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 4 mutations in BRCA1 (c.548-?_4185+?del, c.2296-2297delAG, c.3598C>T and c.4327C>T) and 3 in BRCA2 (c.519+5_519+8delGTAA, c.1796-1800delTT-TAT and c.4111C>T) were present in women with earlyonset BC and no family history of the disease [48,50]. In the Mexican patients unselected for family history, 36 different BRCA mutations were described (20 in BRCA1 and 16 in BRCA2) [50,51]. Of these, 12 were also present in cohorts A or B (Table 3).…”
Section: The Scope Of Brca1 and Brca2 Mutations In Central And South mentioning
confidence: 99%
“…Villarreal-Garza et al found that 14 (15%) mutation cases including founder BRCA1 ex9-12del large rearrangement accounted for 29%, higher prevalence of other large rearrangement and HISPANEL panel accounted for 77% of all the BRCA mutations in 96 unselected Mexican women (Mexico DF) with BC [53], and in a later study Villarreal-Garza et al reported that seven mutations and BRCA1 ex9-12del accounted for 89 and 41% of a total of 44 BRCA mutations in 190 <50 years Mexican women (Mexico DF) with TNBC [54]. Three studies performed in Colombian (Bogotá city) in high risk for breast or ovarian cancer women described five recurrent founder mutations: BRCA1 c.3331 3334delCAAG (the most frequent), BRCA1 c.5123C>A, BRCA2 c.2808 2811del4, BRCA2 6076 delGTTA and BRCA2 c.6275 6276delTT [40][41]55].…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%